Genotoxic exposures of potroom workers - Carstensen, U.; Yang, K.; Levin, Jan-Olof; Östman, C.; Nilsson, Tohr; Hemminki, Kari; Hagmar, Lars (Scandinavian Journal of Work, Environment & Health, 1999)
' ' OBJECTIVES ': 'Potroom workers in aluminum reduction plants have increased risks for bladder and lung cancer due to exposure from polycyclic aromatic hydrocarbons (PAH). In this study correlations between measures of the external, internal, and biological effective dose have been studied for PAH.' ' METHODS ': 'Venous blood samples were obtained from 98 male potroom workers and 55 unexposed male blue-collar workers, for the analysis of aromatic adducts to DNA (deoxyribonucleic acid) in lymphocytes, using the 32P-postlabeling technique. 1-Hydroxypyrene in urine was analyzed with high-pressure liquid chromatography. Personal sampling of both particulate and gas phase PAH was performed during a full workday for the potroom workers and for 5 referents. Individual PAH congeners were determined with liquid chromatographic-mass spectrometric and gas chromatographic-mass spectrometric techniques.' ' RESULTS ': 'The respiratory-zone airborne level of the sum of 22 particulate (median 13.2 mg/m3) and the 7 gas phase PAH-congeners (median 16.3 mg/m3) among the potroom workers was a hundred times higher than among the referents. The urinary concentration of 1-hydroxypyrene before work was 30 times higher for the potroom workers (median 3.43 mmol/mol creatinine) than for the referents. Most airborne PAH congeners correlated with the excretion of 1-hydroxypyrene in urine. The frequency of aromatic DNA adducts did not, however, differ between the potroom workers and the referents, and no correlation was found for 1-hydroxypyrene in urine.' ' CONCLUSION ': 'Despite an obvious occupational exposure to PAH, no increase in aromatic DNA adducts in lymphocytes was found among the potroom workers.
Keywords: aluminum reduction plant; biological monitoring; peripheral lymphocyte; personal airborne sampling; urinary metabolite